How macroeconomic factors may influence agricultural program sustainability: Evidence from Cross River state, Nigeria - Hatzenbuehler, Patrick L.; Mavrotas, George (International Food Policy Research Institute, 2017)
We examine the linkages between government institutions within the Nigerian federal government system; the historical funding levels for agricultural programs in the country; the influence of key macroeconomic variables, such as the global oil price, on the fiscal conditions for various government institutions; and the extent to which the effects of those changes are passed-through between levels of government. We use these findings to explore potential mechanisms that can increase the likelihood of sustaining funding for agricultural programs over time.